2012
DOI: 10.3732/ajb.1100249
|View full text |Cite
|
Sign up to set email alerts
|

Assessing allometric models to predict vegetative growth of mango (Mangifera indica; Anacardiaceae) at the current‐year branch scale

Abstract: Leaf area and stem and branch mass of mango current-year branches could be satisfactorily estimated on the basis of branch basal cross-sectional area with cultivar-specific allometric models. The results suggested that, in addition to the heteroscedastic behavior of the variables studied, model accuracy was probably related to the functional plasticity of branches in relation to the light environment and/or to the number of growth units composing the branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…8;2016 Stem and primary branches accounted for the largest proportion of the total aboveground biomass by weight (49.82%). and was fairly similar to those reported earlier (Normand et al, 2007;Normand & Lauri, 2012;Eneji et al, 2013). This component was 47.9% in young plants and showed an increasing trend with age and crossed 50% after 20 years.…”
Section: Component Biomass Distributionsupporting
confidence: 81%
“…8;2016 Stem and primary branches accounted for the largest proportion of the total aboveground biomass by weight (49.82%). and was fairly similar to those reported earlier (Normand et al, 2007;Normand & Lauri, 2012;Eneji et al, 2013). This component was 47.9% in young plants and showed an increasing trend with age and crossed 50% after 20 years.…”
Section: Component Biomass Distributionsupporting
confidence: 81%
“…The number of terminal and non-terminal GUs was recorded for each axis. The leaf area of each axis was estimated from its basal diameter with allometric relationships ( Normand and Lauri, 2012 ). The basal diameter of the trunk and of each scaffold branch of the trees was measured during flowering of cycles 0, 1 and 2, and converted into cross-sectional area assuming a circular section: BCSA (branch cross-sectional area) for scaffold branches and TCSA (trunk cross-sectional area) for trees.…”
Section: Methodsmentioning
confidence: 99%
“…Previous models evaluating the effect of stem diameter in current year branches revealed that they may predict leaf and branch conductivity (Normand and Lauri, 2012; Boudon et al ., 2020). However, this refers to the conductivity of the xylem, which constitutes most of the branch mass.…”
Section: Discussionmentioning
confidence: 99%